Implicações da ação clínica dos acompanhantes terapêuticos nas redes sociais da cidade do Recife - PE - Nascimento, Ananda Kenney da Cunha (2012)
This research had as general objective: understand the Therapeutic Accompaniments‟ (Ats) clinical action, in its different possibilities, in social networks of Recife-PE city, and as specific objectives: describe the activity of the Therapeutic Accompaniments as clinical action modality; describe the different possibilities of the Therapeutic Accompaniments‟ clinical action and understand the experience of the Therapeutic Accompaniments in their clinical action. We make a qualitative study with an existential phenomenological base. As instrument methodological was use the collaborative narrative. At the first moment, each participant expressed individually, themselves freely. In a second moment, were made a group meeting with the same participants, where they were requested to talk about their experiences with each other, favoring a chance of meeting between them. Five Ats who had experience in Recife-PE participated, with mental, physical or both suffering people with difficulty in social integration. When collecting and interpreting the data we used Gadamer's philosophical hermeneutics, which substantiate the whole trajectory of this research and that consists in the understanding that all human comprehension is an interpretation of the historical conditions stemming from the tradition of which he is part. Thus, we arrived at a final narrative that was constructed from the dialogue between the participants, the researcher and the texts of theorists who based this research. As results, from the narratives, bring the AT clinic in its different possibilities with the specificities inherent of their field, from the experience of those who practice it. In this direction, we realize that Ats are included in the following segments of clinical action: clinical accompaniment to clients, private or institutional, formation, supervision and research. However, we found that they are operationalizing segregated actions with works done in small teams. On the other hand, the Ats aim an organization, trough a group experience, wich aims to include and aggregate the class of professionals who are working in the field. This perspective points to the persuit of an even more delimited place wich includes organization, institutionalization, formalization and professionalization of Ats.